Paradigma Ilmiah pada Ilmu Sosial-Budaya Kontemporer - Yusuf, Akhyar (UI Scholars Hub, 2011)
An American philosopher, Thomas Samuel Kuhn (1922-1996) in his books, The Structure of Scientific Revolution (1962) and The Essential Tension; Selected Studies in Scientific Tradition and Change (1977) poses a paradigm of a universal foundation of science which uses a common fact, method, language and criteria. He does not think that even in the realm of the natural sciences, there are differences, more so that there is a paradigm in the humanities including the arts and literature. Kuhn, however, has established a new paradigm for the philosophy of science which he called “the sociology of science” or a social construction, which now is popular as a constructive paradigm. It is developed in the Critical Theory of Adorno, Horkheimer, and Habermas, and in the Postmodern Theory of Lyotard, Derrida, Foucault, and Baudrillard. The paradigm of the social-political and cultural discourses of the seventies, has developed from structuralism of Saussure and Levi Strauss to post-structuralism or deconstructionism of Jacques Derrida and Paul de Mann referring to contemporary or postmodern era. It rejects stable understanding, logocentrism, antibinary, and gives readers ways to understand a text. The methods used is interpretative paradigm, such as philology, Marxist, new historicism, structuralism, psychoanalysis, theory of acceptance, semiotics, deconstruction, and discourse analysis.